(untitled) (Homoeopathy for All, 2026)
The term “Thyroiditis” is derived from a combination of Latin and Greek terminology namely “thyreoeidēs” meaning “shield shaped” and “itis” as “inflammation”. It is a broad term which refers to the inflammation of the thyroid gland and encompasses several clinical disorders. The thyroid gland is a small, butterfly shaped gland located at the front region of the neck underneath the skin. It is an essential gland of the endocrine system and releases hormones like T3 (Triiodothyronine) and T4 (Thyroxine) which supports the metabolic processes, growth and development of the human body.